Cav-1 (Caveolin-1) Deficiency Increases Autophagy in the Endothelium and Attenuates Vascular Inflammation and Atherosclerosis. Issue 6 (June 2020) - Zhang, Xinbo; Ramírez, Cristina M.; Aryal, Binod; Madrigal-Matute, Julio; Liu, Xinran; Diaz, Antonio; Torrecilla-Parra, Marta; Suárez, Yajaira; Cuervo, Ana M.; Sessa, William C.; Fernández-Hernando, Carlos
Abstract : Objective: Endothelial Cav-1 (caveolin-1) expression plays a relevant role during atherogenesis by controlling NO production, vascular inflammation, LDL (low-density lipoprotein) transcytosis, and extracellular matrix remodeling. Additional studies have identified cholesterol-rich membrane domains as important regulators of autophagy by recruiting ATGs (autophagy-related proteins) to the plasma membrane. Here, we investigate how the expression of Cav-1 in the aortic endothelium influences autophagy and whether enhanced autophagy contributes to the atheroprotective phenotype observed in Cav-1–deficient mice. Approach and Results: To analyze the impact of Cav-1 deficiency on regulation of autophagy in the aortic endothelium during the progression of atherosclerosis, we fed Ldlr −/− and Cav-1 −/− Ldlr −/− mice a Western diet and assessed autophagy in the vasculature. We observe that the absence of Cav-1 promotes autophagy activation in athero-prone areas of the aortic endothelium by enhancing autophagic flux. Mechanistically, we found that Cav-1 interacts with the ATG5-ATG12 complex and influences the cellular localization of autophagosome components in lipid rafts, which controls the autophagosome formation and autophagic flux. Pharmacological inhibition of autophagy attenuates the atheroprotection observed in Cav-1 −/− mice by increasing endothelial inflammation and macrophage recruitment, identifying a novel molecular mechanism by which Cav-1 deficiency protects against the progression of atherosclerosis. Conclusions: These results identify Cav-1 as a relevant regulator of autophagy in the aortic endothelium and demonstrate that pharmacological suppression of autophagic flux in Cav-1–deficient mice attenuates the atheroprotection observed in Cav-1 −/− mice. Additionally, these findings suggest that activation of endothelial autophagy by blocking Cav-1 might provide a potential therapeutic strategy for cardiovascular diseases including atherosclerosis. Abstract : Supplemental Digital Content is available in the text.